Mesenchymal Chondrosarcoma in Children and Young Adults: A Single Institution Retrospective Review. (3rd June 2015) - Bishop, Michael W.; Somerville, Jessica M.; Bahrami, Armita; Kaste, Sue C.; Interiano, Rodrigo B.; Wu, Jianrong; Mao, Shenghua; Boop, Frederick A.; Williams, Regan F.; Pappo, Alberto S.; Samant, Sandeep
Abstract : Background . Mesenchymal chondrosarcoma is an aggressive, uncommon histologic entity arising in bone and soft tissues. We reviewed our institutional experience with this rare diagnosis. Methods . We conducted a retrospective chart review on patients with mesenchymal chondrosarcoma over a 24-year period. Clinicopathologic and radiographic features were reviewed. Results . Twelve patients were identified. Nine were females; median age was 14.5 years (1.2–19.7 years). The most common site was the head/neck (7/12). Disease was localized in 11/12 patients (one with lung nodules). Six with available tissue demonstrated NCOA2 rearrangement by FISH. Six underwent upfront surgical resection, and six received neoadjuvant therapy (2 chemotherapy alone and 4 chemotherapy and radiation). All patients received adjuvant chemotherapy (most commonly ifosfamide/doxorubicin) and/or radiation (median dose 59.4 Gy). At a median follow-up of 4.8 years, 5-year disease-free survival and overall survival were 68.2% (95% CI 39.8%, 96.6%) and 88.9% (95% CI 66.9%, 100%). Two patients had distant recurrences at 15 and 42 months, respectively. Conclusion . Aggressive surgical resection of mesenchymal chondrosarcoma with chemoradiotherapy yields excellent local control and may reduce likelihood of late recurrence. Characterization of downstream targets of the HEY1-NCOA2 fusion protein, xenograft models, and drug screening are needed to identify novel therapeutic strategies.